Detecção de resíduos de disparo de arma de fogo em larvas cadavéricas por ICP OES - Motta, Larissa Campos (2018)
The large increase in violent deaths, mainly in Brazil, and the increasing use of firearms to commit such crimes, makes forensic ballistics associated with forensic entomology major allies in criminal investigations. The concentrations of lead (Pb), barium (Ba) and antimony (Sb), characteristic firearm residues (GSR - GunShot Residue), were monitored in fly larvae (immature Chrysomya albiceps). The samples were collected in a female pig corpse killed with three shots fired by a Taurus®, 40-caliber pistol at a short distance (25 to 40 cm), two in the cephalic region and one in the abdominal region, in a period of 2 to 12 days after death, during the winter, under the influence of rainfall and high relative humidity of the air. Thus, the aim of this work was to evaluate the applicability of the inductively coupled plasma optical emission spectrometry (ICP OES) technique for the quantification of Pb, Ba and Sb from GSR in cadaveric larvae in an uncontrolled environment, simulating a real case of homicide. The ICP OES detect and quantify three trace elements of interest, where the concentrations remained practically constant during the putrefaction stage. The lowest concentrations (Pb = 382.26 µg · L-1, Ba = 140.50 µg · L-1, Sb = 39.18 µg · L-1) and highest concentrations (Pb = 522.66 µg · L- 1, Ba = 190.30 µg · L-1; Sb = 56.14 µg · L-1) were found during the third and fifth postmortem days, respectively. The samples were also analyzed by colorimetric test using sodium rhodizonate (Feigl-Suter reaction) presenting negative result for all the solutions obtained from the immatures of Chrysomya albiceps. One hypothesis for the concentrations uniformity of the three elements is that according to the literature, Chrysomya albiceps larvae species may play a role as an intraguild predator of larvae of other species of Diptera, in addition to performing cannibalism. Thus, the ICP OES technique presents greater sensitivity in the quantification of the elements of interest compared to the conventional colorimetric test, showing to be a technique applicable to this type of matrix. The development of such research is of great forensic importance and ICP OES is a technique that presents potential for future application in cases of violent death, where the victim is in initial, moderate and advanced decomposition. In this regard, the development and improvement of efficient methodologies are of great relevance for the elucidation of crimes